Cytokinins affect the stomatal conductance and CO2 exchange of in vitro apple leaves - Dobránszky, J.; Mendler-Drienyovszki, N. (International Journal of Horticultural Science, 2014)
Effects of different cytokinin supplies including two types of aromatic cytokinins, such as benzyl-adenine, and 3-hydroxybenzyladenine applied at two different concentrations (2.0 and 6.0 μM) were studied on water and gas exchange parameters in in vitro apple leaves of ‘Royal Gala’ and ‘Freedom’ scions after 3 weeks of culture. Cytokinin supply affected the stomatal conductance of water vapour, transpiration rate and the sub-stomatal CO2 concentration of leaves. Effect of cytokinin depended on its applied type and concentration, moreover on the apple scion. According to the results, the rate of CO2 exchange itself is not usable for characterization of function of photosynthetic apparatus of in vitro leaves. However, measurements of stomatal conductance of water vapour and transpiration rate seemed to be good indicators for stomatal behaviour of in vitro apple leaves.